Wird der »Osten« zum »Süden«? Der »Herbst des Volkes« und die Zukunft Osteuropas - Przeworski, Adam (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1992)
In retrospect, it is easier to acknowledge the »necessary« collapse of Eastem European socialism than explaining it in terms of what brought it about. The Theory of Totalitarianism had blurred the view on the social dynamics of real-socialist societies, in the course of which the binding-force of state-sustaining ideology had been increasingly eroded over the past decades. In the end, this was also among those in power - hence the bloodless course ofthe uprisings. What will the future hold: flourishing capitalism, as in the case of Spain, or a South-American-type poor capitalism?